Flow boiling in vertical narrow microchannels of different surface wettability characteristics. (June 2017) - Zhou, Kan; Coyle, Carolyn; Li, Junye; Buongiorno, Jacopo; Li, Wei
Highlights: Saturated flow boiling in a high-aspect-ratio mini-gap channel of different surface wettability characteristics. Pressure drop, local heat transfer coefficient, and flow pattern for different surface wettability characteristics were investigated. Local heat transfer coefficients in the annular flow regime first decreased then increased through the test section. Abstract: An experimental investigation of saturated flow boiling in a high-aspect-ratio, one-sided heating rectangular microchannel was conducted with deionized water as the working fluid. The bare silicon wafer bottom surface of the microchannel was hydrophilic with a contact angle of 65° ± 3°, compared with the super-hydrophilic surface deposited by a thin film of 100-nm-thickness silicon dioxide through PECVD with a contact angle less than 5°. In experimental runs the mass fluxes were in the range of 120–360 kg/m 2  s, the wall heat fluxes were spanned from 4 W/cm 2 to 20 W/cm 2 and the inlet vapor qualities were varied from 0.03 to 0.1. Parametric study and flow visualization on pressure drop, local heat transfer coefficient, and flow pattern for surfaces of different surface wettability characteristics were carried out. Measured total pressure drops in single phase and two phase flow experiments agreed well with predicted values. The experimental data points were almost all located in the annular flow regime, and the local heat transfer coefficients approached a constant value and then increased towards the exit along the flow direction. According to flow visualization, the local dryout phenomenon occurred on the untreated hydrophilic surface at high heat fluxes for low mass fluxes, accompanied with deteriorative heat transfer performance, while it was not observed on the super-hydrophilic surface at the identical condition. Meanwhile severe heat transfer deterioration was obtained on the hydrophilic surface with increased inlet vapor quality, while the heat transfer coefficient of the super-hydrophilic surface was relatively constant which outperformed the untreated silicon wafer surface without increased pressure drop penalty.